2015
DOI: 10.1039/c4ra16998k
|View full text |Cite
|
Sign up to set email alerts
|

Semi-transparent silicon-rich silicon carbide photovoltaic solar cells

Abstract: Si-rich SixC1−x films grown at different RSiC fluence ratios were applied as an i-SixC1−x absorbing layer in all Si-rich SixC1−x-based PVSCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…3 Introducing nitrogen impurities has been adapted as one of the most frequent strategies to improve the electrical conductivity of SiC. 6 Therefore, we propose a new type of photovoltaic material based on ternary silicon carbonitride (SiCN) thin films, where effective nitrogenation of SiC films is achieved in one single layer. Previously, we showed that the brittleness of SiC was improved by the addition of nitrogen.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3 Introducing nitrogen impurities has been adapted as one of the most frequent strategies to improve the electrical conductivity of SiC. 6 Therefore, we propose a new type of photovoltaic material based on ternary silicon carbonitride (SiCN) thin films, where effective nitrogenation of SiC films is achieved in one single layer. Previously, we showed that the brittleness of SiC was improved by the addition of nitrogen.…”
mentioning
confidence: 99%
“…11,12 In addition to bandgap widening, the hydrogenated amorphous structure of SiCN alleviates concerns about the expensive fabrication of crystalline cubic SiC 12,13 or increased power consumption to form nanocrystalline silicon quantum dots (QDs) requiring high annealing temperatures. 14,15 We employed electron cyclotron resonance chemical vapour deposition (ECR PECVD) allowing hydrogen incorporation without the need for high temperature and high RF power, 6 which is a problem in some fabrication methods. Another interesting feature of the SiCN-based matrix is the broad range of stoichiometries allowing to tune the light emission properties through careful design of the composition of this ternary structure.…”
mentioning
confidence: 99%
“…The XPS detected energy of Si 2p orbital electron can be affected by the Si-Si, Si-C, C-Si-O and Si-O with different binding energies of 99.5-99.8 eV, 100.3-100.5 eV, 101.7 eV, and 103.5 eV, respectively. [20][21][22][23] As shown in Fig. 4(a)-(c), the XPS spectra of electron energy distribution at Si 2p core levels are appropriately tted by four Gaussian lines to analyze different binding components including Si-Si, Si-C, C-Si-O and Si-O bonds.…”
Section: Resultsmentioning
confidence: 99%
“…[14][15][16][17] It has been shown that the conversion efficiency of the nonstoichiometric S x iC 1-x -based p-n junction can be improved by varying the reactant fluence ratio (R) in plasma-enhanced chemical vapor deposition (PECVD). During PECVD "R" can be defined as: [18,19]…”
Section: Introductionmentioning
confidence: 99%